0660 Periodic Limb Movement During Sleep And The Incidence Of Cardiometabolic Outcomes: The Hypnolaus Study. (12th April 2019) - Hirotsu, Camila; Marques-Vidal, Pedro; Vollenweider, Peter; Heinzer, Raphael; Haba-Rubio, Jose
Abstract: Introduction: Periodic limb movements during sleep (PLMS) are prevalent in the general population, but their association with cardiometabolic disorders are still controversial. This study aimed to evaluate whether PLMS is a risk factor for the incidence of hypertension, diabetes, metabolic syndrome and cardiovascular (CV) events in a middle to older aged general population. Methods: 2, 162 subjects (51.2% women, mean age: 58.8±11.1 years-old) of the population-based HypnoLaus study (Lausanne, Switzerland) underwent a full polysomnography at home and were followed up over 4.1±1.0 years. PLMS index (PLMSI) was determined at baseline, and PLMSI≥15/h was considered as significant. Evaluations at both baseline and follow-up comprised sociodemographic data, laboratory tests, and clinical assessment. Cardiometabolic outcomes included the incidence of hypertension, diabetes, metabolic syndrome and adjudicated CV events. Results: At baseline, participants with PLMSI≥15/h (n=620) presented higher rates of men, elderly, obesity, diabetes, hypertension, metabolic syndrome and history of previous CV events. After excluding participants having each respective cardiometabolic outcome at baseline, PLMSI≥15/h group, when compared to PLMSI<15/h group, presented similar incidence rates of hypertension (20.1% vs 16.0%, p=0.121), diabetes (3.7% vs 2.6%, p=0.189), metabolic syndrome (8.1% vs 7.7%, p=0.793) and CV events (4.6% vs 3.5%, p=0.282), respectively. Multivariate analysis adjusting for confounding factors confirmed the lack of association between PLMSI≥15/h and the incidence of hypertension (OR=1.058 [0.695-1.609]), diabetes (OR=0.876 [0.443-1.732]), metabolic syndrome (OR=0.807 [0.491-1.327]), and CV events (HR=0.797 [0.472-1.344]). Conclusion: In our large middle-age population-based sample, PLMSI≥15/h was not found to represent a risk factor for the development of cardiometabolic outcomes over 4 years of follow-up. Support (If Any): Leenaards Foundation, FBM, and SNF.